InteractoMIX: a suite of computational tools to exploit interactomes in biological and clinical research. (9th June 2016) - Poglayen, Daniel; Marín-López, Manuel Alejandro; Bonet, Jaume; Fornes, Oriol; Garcia-Garcia, Javier; Planas-Iglesias, Joan; Segura, Joan; Oliva, Baldo; Fernandez-Fuentes, Narcis
Abstract : Virtually all the biological processes that occur inside or outside cells are mediated by protein–protein interactions (PPIs). Hence, the charting and description of the PPI network, initially in organisms, the interactome, but more recently in specific tissues, is essential to fully understand cellular processes both in health and disease. The study of PPIs is also at the heart of renewed efforts in the medical and biotechnological arena in the quest of new therapeutic targets and drugs. Here, we present a mini review of 11 computational tools and resources tools developed by us to address different aspects of PPIs: from interactome level to their atomic 3D structural details. We provided details on each specific resource, aims and purpose and compare with equivalent tools in the literature. All the tools are presented in a centralized, one-stop, web site: InteractoMIX (http://interactomix.com ).